Garapan Baru Seni Karawitan Bali dalam Bingkai Estetika Postmodern - Mawan, I Gede; Wardizal, Wardizal (Institut Seni Indonesia Denpasar, 2025)
Purpose: This short article attempts to conduct a discourse on new works of Balinese karawitan art in the realm of postmodern aesthetic studies, one of the disciplines that is developing quite rapidly today. The main problem studied in this article is the forms of postmodern aesthetics in new works of Balinese karawitan art. Research methods: The main data in this article were obtained through field research (observation) in the form of direct observation of the dynamics of the development of Balinese karawitan art. For the purposes of this writing, a literature study was also conducted in the form of tracking various documents, both written and visual. Results and discussion: In the last decade or 10 years there has been a fairly fundamental change in the process of creating new works in Balinese karawitan art. The process of creating new works that have been based on strong traditions has now undergone changes into contemporary (modern) art, postmodern or contemporary art. Implication: The forms or idioms of postmodern aesthetics found in the process of creating new works in Balinese karawitan art include pastiche, parody, kitsch, camp, and schizfrenia.